1998
DOI: 10.1051/analusis:1998136
|View full text |Cite
|
Sign up to set email alerts
|

Determination of macrominerals and trace elements in the algaSpirulina platensis

Abstract: Abstract. The alga Spirulina, in particular Spirulina platensis, an ubiquitous component of sea and ocean with high nutritional content, is considered a potential alimentary source for third world countries affected by heavy famine problems. On other side, Spirulina-based products are nowadays commonly commercialized and recommended by suppliers as health food, diet pills, vitamins supplement etc.. However, a careful nutritional and toxicological evaluation of these products is necessary, since algae show bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 12 publications
(14 reference statements)
5
27
0
2
Order By: Relevance
“…This technique allows to both analyze a very large number of elements (theoretically almost 70 natural elements of the Periodic Table; more realistically about 40 elements) with very good limits of detection (LODs), sensitivity and accuracy [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. About the precision and accuracy of measurements performed on the standard involved in this study, all the found data for the standards are in agreement with the certified values.…”
Section: Importance Of Nuclear Analytical Technique On the Matrixsupporting
confidence: 65%
“…This technique allows to both analyze a very large number of elements (theoretically almost 70 natural elements of the Periodic Table; more realistically about 40 elements) with very good limits of detection (LODs), sensitivity and accuracy [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. About the precision and accuracy of measurements performed on the standard involved in this study, all the found data for the standards are in agreement with the certified values.…”
Section: Importance Of Nuclear Analytical Technique On the Matrixsupporting
confidence: 65%
“…<DL below detection limit, ND no data a From Campanella et al (1998) and Volkman and Brown (2006) species, there were no significant differences in IVPD observed between whole and lipid-extracted microalgae for P. tricornutum (88.7 and 89. …”
Section: Chemical Compositionmentioning
confidence: 99%
“…This is not entirely unexpected because, although microalgae may contain certain elements of interest for nutrition, the inorganic elemental composition (ash) of microalgae (excluding diatoms) is generally much lower (4-20 %) than macroalgae (22-64 %) (McDermid and Stuercke 2003;Volkman and Brown 2006). We could only find two reports that provide data on the elemental content in algal biomass (Campanella et al 1998;Volkman and Brown 2006). Although useful for comparison, the data did not include certain elements and was limited to species which were not part of this study.…”
Section: −1mentioning
confidence: 99%
“…Spirulina sp. has been reported to contain functional groups like sulphonic, carboxylic, phosphate, amide, hydroxyl group, etc., in polypeptide, polysaccharide, vitamin, protein, amino acids, and fatty acids (Campanella et al, 1998;Doke et al, 2005).…”
Section: Ir Analysismentioning
confidence: 99%